Social media and religious change - Gillespie, Marie, 1953-; Herbert, David, 1967-; Greenhill, Anita (Berlin : De Gruyter, 2013)
Amongst books on religion and the internet, this collection is distinctive in addressing the interaction between social and mass media in the construction of contemporary religion and spirituality, and public understandings of them. Topics discussed include the implications of social media for religious authority, the implications of mediatisation for community relations, and the challenges of social media for traditionally bounded religious communities.
7 Radical Islam, Globalisation and Social Media: Martyrdom Videos on the Internet8 Grassroots Religion: Facebook and Offline Post-Denominational Judaism; 9 Truck Stops and Fashion Shows: A Case Study of the Discursive Performance of Evangelical Christian Group Affiliation on YouTube; 10 Bounded Religious Communities' Management of the Challenge of New Media: Baha'í Negotiation with the Internet; 11 Life, Death and Everyday Experience of Social Media; 12 List of Contributors; Index.
Description based on print version record.
Keywords: Change -- Religious aspects; Mass media -- Religious aspects; Mass media in religion; Religion; Social media; Mass media -- Religious aspects; Mass media in religion; Social media; Religion; Change -- Religious aspects; BODY, MIND & SPIRIT / Gaia & Earth Energies; RELIGION / Christianity / General; Electronic books